Integrated bi-directional SiC MOSFET power switches for efficient, power dense and reliable matrix converter assembly - Lasserre, Philippe; Lambert, Donatien; Castellazzi, Alberto (2016)
This paper presents an innovative device packaging and system integration approach aimed at optimizing the electro-thermal, electro-magnetic and thermo-mechanical performance of the switches in a power converter. In particular, the focus is on state-of-the-art commercially available silicon-carbide (SiC) power MOSFETs used within a matrix converter topology. The improvements at switch level over conventional packaging and integration solutions translate into higher efficiency, power density (in terms of volume and weight) and reliability at system level. In view of typical application domains (e.g., renewable energies, solid-state transformation, smart grids, electric transport), requiring harsh environment withstand capability with high reliability and availability levels, an AC-to-AC matrix converter is chosen as a particularly relevant case study. The paper also addresses two aspects of growing relevance: reliable manufacturability and preventive maintenance compatible modular system assembly for reduced impact of single component failure on system availability.